Minority Primary Care Patients With Depression: Outcome Disparities Improve With Collaborative Care Management. Issue 1 (January 2015) - Angstman, Kurt B.; Phelan, Sean; Myszkowski, Mioki R.; Schak, Kathryn M.; DeJesus, Ramona S.; Lineberry, Timothy W.; van Ryn, Michelle
Abstract : Background/Objectives: Racial and ethnic disparities in depression incidence, prevalence, treatment, and outcomes still persist. The hypothesis of this study was that use of collaborative care management (CCM) in treating depressed primary care patients would decrease racial disparities in 6-month clinical outcomes compared with those patients treated with usual primary care (UC). Research Design/Subjects: In a retrospective chart review analysis, 3588 (51.2%) patients received UC and 3422 (48.8%) patients were enrolled in CCM. Logistic regression analyses were used to examine disparities in 6-month outcomes. Results: Minority patients enrolled in CCM were more likely to be participating in depression care at 6 months than minority patients in UC (61.8% vs. 14.4%; P ⩽0.001). After adjustment for demographic and clinical covariates, this difference remained statistically significant (odds ratio=9.929; 95% CI, 6.539–15.077, P ⩽0.001). The 568 minority UC patients with 6-month follow-up PHQ-9 data demonstrated a much lower odds ratio of a PHQ-9 score of <5 (0.220; 95% CI, 0.085–0.570; P =0.002) and a much higher odds ratio of PHQ-9 score of ≥10 (3.068; 95% CI, 1.622–5.804; P <0.001) when compared with the white, non-Hispanic patients. In contrast, the 2329 patients treated with CCM, the odds ratio for a PHQ-9 score of <5 or ≥10 after 6 months, demonstrated no significance of minority status. Conclusions: Utilization of CCM for depression was associated with a significant reduction of the disparities for outcomes of compliance, remission, or persistence of depressive symptoms for minority patients with depression versus those treated with UC.